2023
DOI: 10.3389/fendo.2023.1183586
|View full text |Cite
|
Sign up to set email alerts
|

Role of ADMA in the pathogenesis of microvascular complications in type 2 diabetes mellitus

Abstract: Diabetic microangiopathy is a typical and severe problem in diabetics, including diabetic retinopathy, diabetic nephropathy, diabetic neuropathy, and diabetic cardiomyopathy. Patients with type 2 diabetes and diabetic microvascular complications have significantly elevated levels of Asymmetric dimethylarginine (ADMA), which is an endogenous inhibitor of nitric oxide synthase (NOS). ADMA facilitates the occurrence and progression of microvascular complications in type 2 diabetes through its effects on endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 118 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…However, supplementation may be needed in special medical conditions such as malnutrition, burns, wounds, infections, and diabetes, in which L-Arg levels are lower than in healthy individuals ( 46 – 49 ). Furthermore, a metabolomics study found that asymmetric dimethylarginine (ADMA) is elevated in T2DM patients ( 50 , 51 ). ADMA is an analog of L-Arg that inhibits NO synthesis that impairs endothelial function, which leads to atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, supplementation may be needed in special medical conditions such as malnutrition, burns, wounds, infections, and diabetes, in which L-Arg levels are lower than in healthy individuals ( 46 – 49 ). Furthermore, a metabolomics study found that asymmetric dimethylarginine (ADMA) is elevated in T2DM patients ( 50 , 51 ). ADMA is an analog of L-Arg that inhibits NO synthesis that impairs endothelial function, which leads to atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…One potential connection between ADMA and ischemic cardiomyopathy is the role of ADMA in promoting endothelial dysfunction, leading to vasoconstriction and reducing blood flow and oxygen delivery to the heart muscle [22]. However, this relationship is most probably multifactorial, involving a complex interplay between endothelial dysfunction, oxidative stress, inflammation, impaired NO signaling, fibrosis, remodeling, hemodynamic effects, and associated comorbidities [22,41].…”
Section: Discussionmentioning
confidence: 99%
“…The serum ADMA level was accepted as a marker of endothelial dysfunction because of its high values in coronary artery disease, end-stage renal failure, stroke, hypertension, and DM [98][99][100][101]. In the present moment, there are no drugs targeting ADMA levels in the context of diabetes management [102].…”
Section: Asymmetric Dimethylargininementioning
confidence: 99%